A study on the surface quality and brittle–ductile transition during the elliptical vibration-assisted nanocutting process on monocrystalline silicon via molecular dynamic simulations. Issue 7 (16th January 2017) - Zhu, Bo; Zhao, Dan; Zhao, Hongwei; Guan, Jian; Hou, Pengliang; Wang, Shunbo; Qian, Long
Abstract : Molecular dynamic (MD) simulation was applied to investigate surface quality and brittle–ductile transition of monocrystalline silicon with a diamond tool during elliptical vibration-assisted nanocutting (EVANC) and traditional nanocutting process. Abstract : Molecular dynamic (MD) simulation method was applied to investigate the surface quality and brittle–ductile transition of monocrystalline silicon with a diamond tool during the elliptical vibration-assisted nanocutting (EVANC) and traditional nanocutting process. In the simulations, the interaction between silicon atoms in the specimen was modeled by the Tersoff potential, whereas the Morse potential was for the description of the interactions between silicon atoms in the specimen and carbon atoms in the diamond tool. In this study, we discovered that EVANC not only changed the brittle-mode cutting into the ductile-mode cutting, but also made the phase transformation layer thinner than that in the traditional nanocutting, which leads to a better surface finish and a large rate of removal of materials. Herein, stress analysis showed that the stress-affected region of the workpiece processed by EVANC was smaller than that of the workpiece processed by the traditional nanocutting. The temperature also increased during the EVANC process. This may soften the silicon material and make the cutting easier. In EVANC, the tangential force and normal force decreased because of the change in the brittle–ductile transition. From the simulation results, EVANC removed the material in the ductile mode, which could increase the removal rate, improve the surface finish, and decrease the cutting force to reduce the tool wear. In conclusion, EVANC has positive effects on the machinability and surface finish of the silicon material.